TALENT MANAGEMENT MODEL ANALYSIS AT PT INDUSTRI KERETA API (PERSERO) - Prayogo, Prayogo; Giyanto, Bambang; Rajab, Ridwan (Jurnal Apresiasi Ekonomi, 2023)
The success of an organization in achieving its goals depends on the quality of the human resources working in it. The key role of human resource management (HRM) in an organization is inherently not only about managing but also finding ways to unlock the potential of creative and innovative people. Talents are the best employees, have competence, high performance, and superior performance, which are developed through career development, and are prepared to become future leaders that determine the company's sustainability. Talent management is the process of planning, mapping, and managing to build and retain talent based on performance assessments, competency measurements, and assessments used as talent indicators. This study aims to analyze the implementation of the talent management program and design appropriate talent management strategies and models at PT INKA (Persero). The research approach used in this study uses a qualitative approach to describe a condition and condition of talent management. This study's data collection used interviews, observation, and documentation studies. The results of this study indicate that PT INKA (Persero) has implemented talent management. However, in terms of implementation, talent management has not been considered effective and appropriate for PT INKA (Persero) because it does not yet have Key Performance Indicators and data related to the talent management system, so companies find it difficult to carry out supervision. The program strategy and talent management model at PT INKA (Persero) has not been fully implemented because they are still in the drafting stage and have not been outlined as a board of directors regulation. So its application is still inconsistent because each function of the talent management dimension still works independently, and there is no continuity between the dimensions of talent management.